Dosis de nitrógeno en las características vegetativas y rendimiento del forraje de Tithonia diversifolia. botón de oro. Loreto - Villacorta Huanuiri, Arisbelith (2024)
Producing quality forage with good protein content is a challenge that the Faculty of Agronomy seeks with the present work entitled NITROGEN DOSE IN THE VEGETATIVE CHARACTERISTICS AND FORAGE YIELD OF Tithonia diversifolia. BOTÓN DE ORO. LORETO. under humid tropical conditions. With a completely randomized block design with four treatments and four repetitions, where the treatments are T0 (control), T1 (100 kilos of nitrogen/ha), T2 ((200 kilos of nitrogen/ha) and T3 (300 kilos of nitrogen/ha), obtaining the following results that the Tithonia diversifolia when applying a greater amount of nitrogen increases the dependent variables, under our agroclimatic conditions of the area. The research shows that the highest dose was the T3 treatment (300 kilos of nitrogen/a) the greatest height with 1.65 meters, green matter of 4.01 kilos per square meter, dry matter of 0.80 kilos per square meter, leaf weight of 1.49 kilos per square meter and stem weight of 2.53 kilos per square meter. The green matter yield was 40,100 kilos per hectare with the aerial biomass treatment with T3 (300 kg of nitrogen/ha).